The Pharmaceutical Ability of Pistacia lentiscus L. Leaves Essential Oil Against Periodontal Bacteria and Candida sp. and Its Anti-Inflammatory Potential - Milia, Egle; Usai, Marianna; Szotáková, Barbora; Elstnerová, Marie; Králová, Věra; D'hallewin, Guy; Spissu, Ylenia; Barberis, Antonio; Marchetti, Mauro; Bortone, Antonella; Campanella, Vincenzo; Mastandrea, Giorgio; et al. (Antibiotics (Basel, Switzerland), 2020)
BACKGROUND: Given the increasing request for natural pharmacological molecules, this study assessed the antimicrobial capacity of Pistacia lentiscus L. essential oil (PLL-EO) obtained from the leaves of wild plants growing in North Sardinia (Italy) toward a wide range of periodontal bacteria and Candida, including laboratory and clinical isolates sp., together with its anti-inflammatory activity and safety. METHODS: PLL-EO was screened by gas chromatography/mass spectrometry. The minimal inhibitory concentration (MIC) was determined. The anti-inflammatory activity was measured by cyclooxygenase (COX-1/2) and lipoxygenase (LOX) inhibition, while the antioxidant capacity was determined electro-chemically and by the MTT assay. The WST-1 assay was used to ascertain cytotoxicity toward four lines of oral cells. RESULTS: According to the concentrations of terpens, PLL-EO is a pharmacologically-active phytocomplex. MICs against periodontal bacteria ranged between 3.13 and 12.5 µg/ml, while against Candida sp. they were between 6.25 and 12.5 µg/mL. Oxidation by COX-1/2 and LOX was inhibited by 80% and 20% µg/mL of the oil, respectively. Antioxidant activity seemed negligible, and no cytotoxicity arose. CONCLUSIONS: PLL-EO exhibits a broad-spectrum activity against periodontal bacteria and Candida, with an interesting dual inhibitory capacity toward COX-2 and LOX inflammatory enzymes, and without side effects against oral cells.
Keywords: Candida albicans; medicinal herbs; Candida glabrata; Oral health care products; periodontal disease; cyclooxygenase; lipoxygenase